2010
DOI: 10.1111/j.1365-2699.2010.02294.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical patterns of freshwater micro‐ and macroorganisms: a comparison between phytoplankton, zooplankton and fish in the eastern Mediterranean

Abstract: Aim We investigated the biogeographical patterns of phytoplankton, zooplankton and fish in freshwater ecosystems. We tested whether spatial distance or environmental heterogeneity act as potential factors controlling community composition.Location Northern and central Greece, eastern Mediterranean.Method Data on 310 phytoplankton, 72 zooplankton and 37 fish species were collected from seven freshwater systems. Species occurrence data were used to generate similarity matrices describing community composition. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 52 publications
4
41
0
1
Order By: Relevance
“…It has been shown that macroorganisms have obvious zonal distributions along gradients of water and energy [3]. Whether or not microorganisms follow similar distribution patterns to macroorganisms is still a matter of debate [4], although we have benefited from recent advances in molecular biological techniques which make it possible to examine geographic distributions of microbes [1], [5], [6]. Some interesting studies on bacterial communities have been undertaken through comparative studies across different habitats [7][9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that macroorganisms have obvious zonal distributions along gradients of water and energy [3]. Whether or not microorganisms follow similar distribution patterns to macroorganisms is still a matter of debate [4], although we have benefited from recent advances in molecular biological techniques which make it possible to examine geographic distributions of microbes [1], [5], [6]. Some interesting studies on bacterial communities have been undertaken through comparative studies across different habitats [7][9].…”
Section: Introductionmentioning
confidence: 99%
“…The observed spatial patterns of each microbial community could be influenced by potential factors related to its own ecological characteristics and requirements (Soininen et al 2011). Although bacterial and microeukaryotic communities responded to the same environmental conditions, the different population abundance, generation time, and organism size of each community have led to different speciation, extinction, or dispersal rates (Mazaris et al 2010;Yang et al 2010;Hanson et al 2012). Clearly, variations in both bacterial and microeukaryotic communities responded to the same environmental factors with an exception of DO in this study.…”
Section: Spatiotemporal Patterns Of River Ecosystemmentioning
confidence: 98%
“…The high contribution of cyanobacteria species to phytoplankton diversity has been commonly observed in eutrophic lakes in Greece (e.g., Moustaka-Gouni, 1993;Mazaris et al, 2010) and worldwide (e.g., . Cyanobacteria species were found to be associated with artificial and agricultural land use types such as urban and artificial sites and permanent crops.…”
Section: Discussionmentioning
confidence: 93%
“…Evidence from recent studies performed at the same region demonstrated that phytoplankton species occurrence and diversity is largely affected by environmental heterogeneity (Mazaris et al, 2010). Evidence from recent studies performed at the same region demonstrated that phytoplankton species occurrence and diversity is largely affected by environmental heterogeneity (Mazaris et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation